A 7-Level Single DC Source Cascaded H-Bridge Multilevel Inverter with a Modified DTC Scheme for Induction Motor-Based Electric Vehicle Propulsion. (14th February 2013) - Khoucha, Farid; Marouani, Khoudir; Benbouzid, Mohamed; Kheloui, Abdelaziz; Mamoune, Abdeslam
Abstract : This paper presents a new hybrid cascaded H-bridge multilevel inverter motor drive DTC scheme for electric vehicles where each phase of the inverter can be implemented using a single DC source. Traditionally, each phase of the inverter requires n DC source for 2 n + 1 output voltage levels. In this paper, a scheme is proposed that allows the use of a single DC source as the first DC source which would be available from batteries or fuel cells, with the remaining (n − 1 ) DC sources being capacitors. This scheme can simultaneously maintain the capacitors of DC voltage level and produce a nearly sinusoidal output voltage due to its high number of output levels. In this context, high performances and efficient torque and flux control are obtained, enabling a DTC solution for hybrid multilevel inverter powered induction motor drives intended for electric vehicle propulsion. Simulations and experiments show that the proposed multilevel inverter and control scheme are effective and very attractive for embedded systems such as automotive applications.